INTERACTIVE HOTSPOT BILLING SYSTEM MENGGUNAKAN METODE PROTOYPING BERBASIS WEB DAN SMS GATEWAY STUDI KASUS FAKULTAS SAINS DAN MATEMATIKA UNIVERSITAS DIPONEGORO - Moch. Amri Wildan; Eko Adi Sarwoko; Helmie Arif Wibawa (Jurusan Ilmu Komputer / Informatika, FMIPA UNDIP, Semarang, 2013)
The number of internet users academics Faculty of Science and Mathematics University of Diponegoro via wireless is increasing, therefore it is necessary to Hotspot Billing can help network administrators to manage. Hotspot Billing is interactive, so users do not have contact hotspot with the administrator directly. Users can manage their account, obtain statistical information, and can complain to an administrator with easy access via the web and sms. This Software was built using a programming language Hypertext Preprocessor (PHP) and MySQL database management system that is integrated with the Remote Authentication Dial-In User Service (RADIUS) Server, and supported by the SMS Gateway